KARAKTERISTIK KONSTANTA DAN KONDUKTIVITAS OPTIK DAUN BIDARA (ZIZIPHUS MAURITIANA) PADA SUHU MICROWAVE MENGGUNAKAN SPEKTROSKOPI UV-VIS (ULTRA VIOLET-VISIBLE) - Jumardin, Jumardin (SAINFIS: Jurnal Sains Fisika, 2023)
Bidara leaf (Zizyphus mauritania) which have been extracted and irradiated with the microwave method at temperatures of 150 0C, 200 0C and 250 0C produced the parameter values of optical density (OD), reflectance (%R), index of refraction (n), coefficient of extension ( k), optical conductivity (σopt), urbach energy (Eu) and optical dielectric constant (ε). The results showed that changes in microwave temperature could affect the optical parameter values of bidara leaf extract. The value of optical density (OD), reflectance (%R) and Urbach energy (Eu) increase with increasing absorption coefficient (α), while the value of the refractive index (n), optical conductivity (σopt), optical dielectric constant (ε) decreases by variable temperature and shift in absorption wavelength of bidara leaf extract. The increase and decrease in optical parameters were caused by changes in molarity properties and structural irregularities in the molecular properties of bidara leaf extract after microwave temperature treatment. The value of optical conductivity is based on the absorption coefficient (α), index of refraction (n) and speed of light, while the value of the optical dielectric constant (ε) is based on changes in the index of refraction (n) and the extension constant (k).